Maximum Power Point Tracking in Solar Power Plants under Partially Shaded Condition - Pikutis, M.; Vasarevicius, D.; Martavicius, R. (Elektronika ir Elektrotechnika, 2014)
Efficiency of solar cells is the biggest when the controller adjusts the load according to the temperature of the solar cell and solar energy flux. This task is accomplished by various maximum power point tracking (MPPT) algorithms. This paper presents the analysis of maximum power point tracking efficiency, when some modules of the solar power plant are partially shaded. Mathematical models of photovoltaic module and Incremental Conduction (IncCond) algorithm are implemented in Matlab/Simulink environment. The simulation is performed using saved solar power flux signal, imitating real-world environmental conditions. This signal allows to compare different working modes of MPPT tracker and to calculate the efficiency of the algorithm. It is proposed to use artificial neural network (ANN) to increase the efficiency of (IncCond) algorithm. Using ANN allows faster maximum power point tracking. DOI: http://dx.doi.org/10.5755/j01.eee.20.4.6677